The influence of MLM companies and agent attributes on the willingness to undertake multilevel marketing as a career option among youth - Nga, Joyce Koe Hwee *; Soo, W. M. (Emerald, 2011)
Purpose – The direct selling industry is experiencing phenomenal growth in Malaysia. The Domestic Trade, Cooperatives and Consumerism Ministry projects that there will be a 20 percent increase in volume of direct sales growth to RM5.5 billion in 2010, RM6.2 billion in 2011 and RM7 billion in 2012. The Direct Selling Act 1993 has been reinforced to accord protection to potential consumers. With the real wages in Malaysia decreasing and increasing unemployment especially among fresh graduates there may be a greater incentive to explore multilevel marketing (MLM) to supplement their income and maintain their desired modern lifestyle. However, the perception of MLM has in the past been tainted by unscrupulous pyramid and Ponzi schemes which aims at quick profits and are not sustainable. This paper aims to investigate the influence of perception of MLM companies and agent attributes on the willingness to undertake MLM as a career among youth. Design/methodology/approach – The sample of this study comprised 218 students pursuing business and management degrees at a private higher education institution in Klang Valley, Malaysia. Methodologically, this study developed statistically valid and reliable scales for all the constructs of this study namely perception of attributes of MLM companies (general, schemes and service) an agents (general and trust) as well as willingness to undertake MLM as a career option. Findings – The findings indicate that all MLM company and agent attributes have a significant influence on the willingness to undertake MLM as a career option except MLM schemes. General agent attributes displayed a significant negative influence. Practical implications – MLM companies need to make their schemes more understandable and transparent to solidify the legitimacy and sustainability as the employer of choice. Originality/value – The paper shows that MLM remains a viable career option for youth and they need to be equipped with adequate training in personal selling, entrepreneurship and soft skills. MLM companies can tap and nurture this pool of young talent to meet their human resource needs for future growth of this industry in Malaysia.